Alberta's Construction Labour Relations During the Recent Downturn - Fisher, E.G.; Kushner, Stephen (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1986)
This paper describes and analyses from a labour relations perspective the rapid changeover of Alberta's construction industry from 70-80% unionized projects during 1975-1982 to a 5-10% coverage of projects by collective agreements commencing in 1984.